Estimates of jaguar (Panthera onca) population density in the South American Greater Madidi-Tambopata Landscape - Ayala, Guido Marcos (2022)
Abstract [Introduction]: The jaguar (Panthera onca) is the largest feline in the Americas, and due to vast connected forests the Amazon currently holds the largest jaguar populations. [Objective]: We present jaguar population density estimates for seven sites in the Great Madidi-Tambopata Landscape in northwestern Bolivia and southeastern Peru. [Methodology]: Data collection occurred from 2001 to 2008, using between 26 to 118 camera trap stations distributed in polygons between 37 to 355 km2 of sampled area, active from 29 to 75 days at each study site. [Results]: We identified a total of 63 individuals across all sampling sites. The estimated capture rate for each sampling site ranged from 0.18 to 2.81 independent events/100 trap nights. Jaguar density estimates with SCR models ranged from of 0.1 to 2.39 individuals/100 km2, and derived CAPTURE (MMDM) population density estimates using a regional buffer (5.76 km, n = 19), were between 0.52 and 2.86 individuals/100 km2. [Conclusions]: These results are especially relevant for the development of conservation strategies and evaluations for this threatened species, and also underline the importance of the transboundary Greater Madidi-Tambopata Landscape as a population stronghold for jaguars in the region.